Business Processes Outsourcing in Building Enterprises - Chernysh, Iryna; Glebova, Alla; Maksymenko, Oleh (International Journal of Engineering and Technology, 2018)
The article explores the role and importance of outsourcing for managing business processes at enterprises of the construction industry. Since the main purpose of managing construction enterprises is to achieve high technical and economic indicators, compliance with the terms of construction of objects and their construction, ensuring an increase in profitability and profitability of operations in the long-term perspective. This is possible with the use of outsourcing, which, unlike subcontracting, is aimed at providing profitability by concentrating on the performance of priority activities for which the construction company has the highest level of competence. Also, outsourcing involves taking risks and responsibilities of an outsourcing company for the quality of running business processes. This is a significant difference from the subcontract works and allows forming the long-term competitive advantages of the construction enterprise.Â Â